Pelaksanaan Pekerjaan Finishing pada WC dan Tempat Whudu Masjid A-Ikhlas Thumburuni Kab. Fakfak Papua Barat - Rusdin, Rusdin; Mangopo, Merlyn; Yarkuran, Ruslan R (Community Engagement and Emergence Journal (CEEJ), 2021)
Al-Iklas Mosque is one of the public mosques in Fakfak City which is still active and has a fairly large number of worshipers, namely 300 people. However, currently the mosque has supporting facilities for building facilities, namely toilets and ablution places whose floors and walls have not been tiled and painted. As well as the damage to water channels and faucets where wudu. Therefore, the PKM team provided solutions to carry out work on installing ceramic floors, repairing drains and painting the walls of the WC and the ablution area of ??the Al-Iklas Thumburuni Fakfak Mosque. The method used is the first method, the ceramic installation service method is by immersing ceramics, installing ceramics by applying cement to the floor to which ceramics will be affixed and applying ceramic grout. The second method, the method of painting the walls, is by cleaning the walls first, mixing the paint with a water base or solvent, and using the zigzag technique in painting. The third method, the method of repairing the water channel where the wudu is located, is by welding the iron pipe which is damaged and leaking. So in this finishing work, collaborating using 2 disciplines from the POLINEF institution, namely civil engineering, namely ceramic installation and painting work, while machine maintenance techniques, namely plumbing repair work. Keywords: Ceramic Installation, Painting Work, Plumbing Welding Work. Al-Iklas Mosque, Fakfak